The Effect of Active Learning Strategy The Great Wind Blows Type of Student Learning on Material Results in Limit to Class XI MA Siti Mariam - wati, Fatma (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2016)
This type of research is a field research (field research) with quantitative approach. This study used an experimental method that is pre-experimental design. The study population was students grade XI MA Siti Mariam, and sampling using sampling saturated. Data analysis techniques in this research is descriptive statistics, normality test, heteroscedasticity test and simple linear regression. The results show that there is active learning strategies influence the type of the great wind blows toward student learning outcomes in the material in the limit of infinite grade XI MA Siti Mariam 2015/2016 school year, as indicated by thitung> t table (6.532> 2.120) and the regression coefficients X amounted to 0.632 states that any type of active learning strategies influence the great wind blows (X) rose unit then learning results in an infinite limit students will increase by 0.632 units. In R2 test known type of active learning strategies the great wind blows has the effect of 73% for improved learning outcomes in infinite limit. Keywords: influence, active learning, the great wind blows, the limit at infini